A new combination of naringin and trimetazidine protect kidney Mitochondria dysfunction induced by renal Ischemia / Reperfusion injury in rat - Negin Amini; Mohammad Badavi; Mehdi Goudarzi (Brazilian Journal of Pharmaceutical Sciences, 2022)
Abstract Ischemia/reperfusion (IR) injury leads to overproduction of Reactive Oxygen Species (ROS), and disrupts membrane potential that contributes to cell death. The aim of this study was to determine if naringin (NAR), trimetazidine (TMZ) or their combination, protect the kidney mitochondrial from IR injury. Forty rats were randomly allocated into five groups, harboring eight rats each: Sham, IR, NAR (100 mg/kg), TMZ (5 mg/kg) and NAR plus TMZ. Ischemia was induced by obstructing both renal pedicles for 45 min, followed by reperfusion for 4 hours. The mitochondria were isolated to examine the ROS, Malondialdehyde (MDA), Glutathione (GSH), mitochondrial membrane potential (MMP) and mitochondrial viability (MTT). Our findings indicated that IR injury resulted in excessive ROS production, increased MDA levels and decreased GSH, MMP and MMT levels. However, NAR, TMZ or their combination reversed these changes. Interestingly, a higher protection was noted with the combination of both, compared to each drug alone. We speculate that this combination demonstrates a promising process for controlling renal failure, especially with the poor clinical outcome, acquired with NAR alone. This study revealed that pretreatment their combination serves as a promising compound against oxidative stress, leading to suppression of mitochondrial stress pathway and elevation of GSH level.